2020
DOI: 10.15255/kui.2019.024
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of “Neural Networks and Multiple Linear Regressions” Models to Describe the Rejection of Micropollutants by Membranes

Abstract: A rejection process of organic compounds by nanofiltration and reverse osmosis membranes was modelled using the artificial neural networks. Three feed-forward neural networks based on quantitative structure-activity relationship (QSAR-NN models) characterised by a similar structure (twelve neurons for QSAR-NN<sub>1</sub>, QSAR-NN<sub>2</sub>, and QSAR-NN<sub>3</sub> in the input layer, one hidden layer and one neuron in the out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…The two extreme layers correspond to the input layer which receives its inputs from the outside environment on the one hand and to the output layer which provides the result of the treatments carried out on the other hand. The intermediate layers are called hidden layers, their number is variable (Ammi et al 2020;Khaouane et al 2013;Meshram et al 2020). The feedforward neural networks can be given as follow for the prediction of the polar pharmaceutical With: i (i = 1: n=13) is the number of neurons in the input layer, j (j = 1:m) is the number of neurons in the output layer, k (k = 1) is the number of neurons in the output layer, 𝑥 𝑖 is the inputs of the FNN,…”
Section: Feedforward Neural Network (Fnn)mentioning
confidence: 99%
See 1 more Smart Citation
“…The two extreme layers correspond to the input layer which receives its inputs from the outside environment on the one hand and to the output layer which provides the result of the treatments carried out on the other hand. The intermediate layers are called hidden layers, their number is variable (Ammi et al 2020;Khaouane et al 2013;Meshram et al 2020). The feedforward neural networks can be given as follow for the prediction of the polar pharmaceutical With: i (i = 1: n=13) is the number of neurons in the input layer, j (j = 1:m) is the number of neurons in the output layer, k (k = 1) is the number of neurons in the output layer, 𝑥 𝑖 is the inputs of the FNN,…”
Section: Feedforward Neural Network (Fnn)mentioning
confidence: 99%
“…Ratio "RER" provided by Viscarra Rossel: excellent predictions (RER and RPD > 2.5); good (RER and RPD of 2.0 to 2.5); approximate quantitative predictions (RER and RPD of 1.8 to 2.0); possibility to distinguish high and low values (RER and RPD of 1.4 to 1.8); and unsuccessful (RER and RPD < 1.40) (Ammi et al 2020;Rossel et al 2006).…”
Section: Evaluation Criteriamentioning
confidence: 99%
“…On the other hand, we adopted the five-level interpretations of Residual Predictive Deviation "RPD" and Range Error Ratio "RER" provided by Viscarra Rossel: excellent predictions (RPD and RER > 2.5); good (RPD and RER of 2.0 to 2.5); approximate quantitative predictions (RPD and RER of 1.8 to 2.0); possibility to distinguish high and low values (RPD and RER of 1.4 to 1.8); and unsuccessful (RPD and RER < 1.40) [22,41]. The RPD and RER of the ANNs and SVM models are higher than 2.5 (RPD = 8.4808% and RER = 54.5525% for ANN; RPD = 6.8644% and RER = 15.3455% for SVM) for the total phase.…”
Section: Comparison Of Modelsmentioning
confidence: 99%
“…However, there have been few models of ANNs due to the complexity of mechanisms to predict the rejection of organic compounds by NF/RO [15][16][17][18][19][20][21][22]. There is no modeling study for the rejection of organic compounds by NF/RO membranes using SVMs.…”
Section: Introductionmentioning
confidence: 99%
“…(Sarafraz & Hormozi 2014) shown that fouling resistance represents the linear/asymptotic behavior with time in force convective and nucleate boiling heat transfer regions, by studying experimentally the influence of different operating parameters such as dilute concentrations of nanofluid (by weight), heat flux and mass flux on the single phase, two-phase flow-boiling and particulate fouling resistance of CuO/EG nanofluid. Artificial Neural Network (ANN) technique has been used in many scientific domains such as (solar, nucleate boiling, solubility of solid drugs, methodology, Biofuels, Micropollutants) (Laidi and Hanini 2013;Mohamedi et al 2015;Rezrazi et al 2016;Abdallahelhadj et al 2017;Ammi et al 2020;Belmadani et al 2020), and it has proven its reliability and robustness by establishing the relationship between the variables without considering the detailed physical process. This feature of ANN encourages its use for predicting of thermophysical properties of nanofluids.…”
Section: Introductionmentioning
confidence: 99%